Evaluating Reporting of Patient-Reported Outcomes in Randomized Controlled Trials Regarding Inflammatory Bowel Disease: A Methodological Study. (December 2022) - McIntire, Ryan; Waters, Philo; Tanner, David; Dhillon, Jaydeep; Hillman, Cody; Wise, Audrey; Kee, Micah; Anderson, Reece; Ottwell, Ryan; Hartwell, Micah; Vassar, Matt
Patient-reported outcomes (PROs) in randomized controlled trials pertaining to inflammatory bowel disease are important in identifying patients' perspective of treatment. Incompletely reported PROs within trials could misrepresent information for clinicians and may contribute to treatment which lacks accommodation of patient input. Our study evaluates completeness of reporting of PROs and risk of bias (RoB) to identify how well trialists are adhering to known resources for trials. We used MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials to identify eligible trials from 2006 to 2020 with at least 1 PRO measure related to inflammatory bowel disease. The trials were screened in duplicate using Rayyan. We then compared trial completion of reporting to the Consolidated Standards of Reporting Trials (CONSORT)-PRO adaptation, and assessed RoB using the Cochrane Collaboration RoB 2.0 tool. To measure trial and reporting characteristics, we performed bivariate regression analyses. Among a sample of 29 trials, the mean completion percentage for CONSORT-PRO was 46.77%. We found PROs as a secondary outcome had significantly lower CONSORT-PRO reporting (p<0.05). In addition, per cent completeness of reporting was significantly higher with both a 'therapy' intervention, and trials published following the development of CONSORT-PRO (p<0.05). Incomplete PRO reporting is common in trials focused on inflammatory bowel disease. This suboptimal reporting indicates the need for adherence to reporting guidelines. Trialists should use the CONSORT-PRO checklist, as endorsed by Patient-Reported Outcomes Tools: Engaging Users and Stakeholders, to assess their studies in order to enhance reporting adherence.